Community Health Clinic Implementation of a Medication Assisted Treatment program for Opioid Use Disorder - Cruz, Amanda (My University, 2020)
The opioid epidemic is affecting every aspect of communities, from the national level down to each state and city level. North Carolina reports over 50 percent of deaths being related to heroin and synthetic narcotics. There are many different treatment options for opioid addiction, however research evidence supports that medication assisted treatment (MAT) has the most successful rates of long-term sobriety. Unfortunately, MAT programs can be scarce and expensive. A quality improvement project was designed to assist a community clinic in developing an outpatient MAT program. The clinic was awarded a Health Resources and Services Administration (HRSA) grant to support the creation of a MAT program. The project included the development of a cost benefit analysis, a patient’s screening questionnaire, an admission protocol, an evaluation tool utilizing the plan-do-study-act (PDSA) model, a substance use history and physical form for use by the providers, a patient information brochure, and marketing materials for the MAT program. Throughout the project, marketing of the program and the clinic to the community became the primary focus. Once marketing strategies regarding the MAT program were implemented, an increase in patient admissions to the outpatient treatment program occurred. This project addressed access to care objectives related to Healthy People 2020, the North Carolina Opioid Action Plan, and the Institute for Healthcare and Improvement.
Keywords: opioid addiction, medication assisted treatment, community health clinic, addiction, addiction treatment, opiate addiction, buprenorphine/naloxone, heroin addiction